On variations for mappings with restrictions on dilation in measure - Potemkin, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct variations for classes of homeomorphisms with generalized derivatives in the case where restrictions in measure of general form are imposed on large values of dilation. We use the method for the construction of variations suggested by Gutlyanskii.